KEBIJAKAN PEMERINTAH DALAM PEMBANGUNAN DI DESA SEREANG KECAMATAN MARITENGNGAE KABUPATEN SIDENRENG RAPPANG - Mursalim S (PRAJA: Jurnal Ilmiah Pemerintahan, 2018)
This study aims to find out How Government Policies in Development In Rural District of Maritengngae Sidenreng Sereang Rappang. The population in this study are all Sereang Village community, with a population of 2,040 people. The desired sample the researcher is 10% or 180 people, taken by purposive sampling technique. This type of research is a quantitative and descriptive type of research is experimental. Data collection techniques used in this study is the observation, questionnaire and literature study. The collected data is then used by means of data analysis techniques with SPSS 16.0 for Windows. The results of such analysis Descriptive Statistics, Quality Test Data, Test Assumptions Classic, Simple Regression Analysis and Testing Hypotheses, using a Likert Scale. The results of this study indicate that the village government policy is 54% of the produced. While the expected results was 100%. seen from the results of the questionnaire data if any questions indicator variable (X) of the Policy. and the development of the village is 71% of the produced. While the expected results was 100%. seen from the results of the questionnaire data if any questions indicator variable (Y) Development. The village government policies significantly affect pembagunan village, with a probability value was under 0:05 dilhat of tcount> table value to the value of 6,971> 1,040. That is, automatically Ha Ho accepted and rejected explaining that a significant regression coefficient or policy variable (X) significantly influence the development (Y). That is, automatically Ha Ho accepted and rejected explaining that a significant regression coefficient or village government policy variables significantly influence the development of the village.